2019
DOI: 10.1002/cnma.201900381
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent CH3NH3PbBr3/β‐Cyclodextrin Core/Shell Nanodots with Controlled Size and Ultrastability through Host‐Guest Interactions

Abstract: Luminescent lead halide perovskite nanocrystals (LHP NCs) have attracted great attention. This work reports the synthesis of well‐defined core/shell structured CH3NH3PbBr3/β‐cyclodextrin (MAPbBr3/β‐CD) nanodots via host‐guest interaction between β‐cyclodextrin and hexylamine. The MAPbBr3/β‐CD nanodots show high luminescence with photoluminescence quantum yields (PLQYs) of 89.7% in solution and 38.0% in solid state. The MAPbBr3/β‐CD nanodots have superior stability in water, under heat and UV light exposure due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…Despite the vulnerability of hybrid perovskites to ambient condition and polar solvents, some recent studies have revealed the use of cyclodextrin, which is a cyclic oligosaccharides, to enhance stability of the polycrystalline perovskite films as well as colloidal crystals via host‐guest interaction. [ 84–89 ] Herein, hybrid perovskite nanocrystals were similarly modified using β‐cyclodextrin (βCD) to endow the nanocrystals with robustness and stability against ambient conditions and solvents during fiber production, and nanocrystals were named as βNC (as illustrated in Figure ), as described in detail in the Experimental Section. The βNC was utilized as a charge–trapping unit, which was directly incorporated into an organic semiconductor that could enhance the charge dissociation and transfer between semiconducting materials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the vulnerability of hybrid perovskites to ambient condition and polar solvents, some recent studies have revealed the use of cyclodextrin, which is a cyclic oligosaccharides, to enhance stability of the polycrystalline perovskite films as well as colloidal crystals via host‐guest interaction. [ 84–89 ] Herein, hybrid perovskite nanocrystals were similarly modified using β‐cyclodextrin (βCD) to endow the nanocrystals with robustness and stability against ambient conditions and solvents during fiber production, and nanocrystals were named as βNC (as illustrated in Figure ), as described in detail in the Experimental Section. The βNC was utilized as a charge–trapping unit, which was directly incorporated into an organic semiconductor that could enhance the charge dissociation and transfer between semiconducting materials.…”
Section: Resultsmentioning
confidence: 99%
“…Distinct characteristic XRD peaks are explicitly observed at a position that is in good agreement with previous studies. [ 84,88 ] To characterize the structural integrity of the perovskite nanocrystals and self‐assembly between surface ligands and perovskite nanocrystals, Fourier transform infrared (FTIR) spectroscopy analysis was performed, as shown in Figure 2b. The characteristic peak positions of the samples corresponding to βCD are consistent with a slight variation in both pure βCD and βCD‐ encapsulated perovskite nanocrystals.…”
Section: Resultsmentioning
confidence: 99%
“…Another study, reported by Huang and co-workers, discussed the fabrication of a methylammonium lead bromide (MAPbBr 3 )/β-cyclodextrin (β-CD) core/shell structure employing a host−guest interaction between the β-CD (a hydrophobic cyclic oligosaccharide) cavity and the aliphatic chain of the hexylamine capping ligand. 58 The authors synthesized the MAPbBr 3 /β-CD core/shell NCs using a simple one-step reprecipitation method. In their approach, a mixture of PbBr 2 , CH 3 NH 3 Br, and hexylamine was dissolved in DMF at room temperature.…”
Section: Synthesis and Stabilitymentioning
confidence: 99%
“…A polymer-based shell was also introduced as one of the routes to form core/shell composite (Figure 8e). Huang et al, formed core/shell structure by coating of β-cyclodextrin (β-CD), which is a cyclic oligosaccharide, on top of the MAPbBr 3 [182]. Capping ligand hexylamine was introduced into the system to realize host-guest interaction reaction.…”
Section: Environmental Stability (Heat Moisture Oxygen Uv Lightmentioning
confidence: 99%